2018
DOI: 10.28976/1984-2686rbpec2018181365
|View full text |Cite
|
Sign up to set email alerts
|

A Metalinguistic Study on the Photon Interpretation Present in Physics Textbooks Approved in PNLDEM 2015: Elements for a Symmetric Sociology of Science Education

Abstract: We present a work on Symmetric Sociology on Science Education from a theoretical framework that articulates Bruno Latour's and Mikhail Bakhtin's Philosophies. We perform a metalinguistic analysis of the texts about Quantum Physics present in the Physics textbook approved by the PNLDEM 2015 in dialogue with the philosophical interpretations about the photon in scientific papers. We present the dialogic relation among the different scientific and didactic speeches, explicating the re-elaboration of meaning that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…A possible way to escape this ontological controversy in QP Education would be to follow the suggestion made by some researchers of relativistic quantum mechanics: there are no particles, only fields [24], [25]. However, the wave-particle duality is still a major theme in contemporary Quantum Physics historiography [15], [26] and its historical and conceptual relevance also motivates contemporary research in Quantum Physics Teaching [27]- [29], besides of being a common subject in Quantum Physics courses in undergraduate and high-school levels [18], [30]. We highlight that this topic may be approached in different trends of Quantum Physics Teaching such as the development of didactic experiments [31]- [36], the use of metaphors [37], [38], production of tutorials [29], [39], [40], the use of computational simulations [41]- [46], the analysis of didactic textbooks [47], [48], and so on .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A possible way to escape this ontological controversy in QP Education would be to follow the suggestion made by some researchers of relativistic quantum mechanics: there are no particles, only fields [24], [25]. However, the wave-particle duality is still a major theme in contemporary Quantum Physics historiography [15], [26] and its historical and conceptual relevance also motivates contemporary research in Quantum Physics Teaching [27]- [29], besides of being a common subject in Quantum Physics courses in undergraduate and high-school levels [18], [30]. We highlight that this topic may be approached in different trends of Quantum Physics Teaching such as the development of didactic experiments [31]- [36], the use of metaphors [37], [38], production of tutorials [29], [39], [40], the use of computational simulations [41]- [46], the analysis of didactic textbooks [47], [48], and so on .…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the authors argue that the analysis of textbooks written in the period of scientific crisis, such as the quantum revolution, has shown that they cannot be seen as a "mausoleum of scientific truths" (as Kuhn would describe it), but that they contributed actively to the scientific development. Furthermore, the narrative of undergraduate textbooks sometimes is so relevant that is more diffused than the original paper narrative [18].…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, é reconhecido que o livro didático apresenta um papel central no processo de formação de cientistas [16] e na formação de professores [17]. Por isso, analisar como livros didáticos apresentam determinado conceito é uma forma prática de entendermos como a comunidade científica vem formalizando essa noçãoproposta que vem sendo discutida desde o trabalho seminal de Thomas Kuhn [18], com diferentes implicações para o Ensino de ciências [19,20].…”
Section: Introductionunclassified